Implementation of School-Based Management at Senior High School of State I Ratahan Timur - Manansang, Denny; Katuuk, Deitje Adolfien; Sumual, Shelty D.M. (JR Education, 2023)
Implementation of School-Based Management (SBM), from time to time, the public's awareness of the urgency of education is increasing and is starting to appear on the surface. The purpose of this study is to describe the implementation of school-based management at Senior High School of State I Ratahan Timur and to describe the obstacles to implementing school-based management at Senior High School of State I Ratahan Timur. Describe the efforts made by the school to overcome the obstacles to the implementation of school-based management that occurred at Senior High School of State I Ratahan Timur. The research method used is the descriptive qualitative method. the research object is the implementation of learning supervision at Senior High School of State I Ratahan Timur, the researcher uses data collection techniques through observation, interviews, and documentation studies. Furthermore, to analyze the data that has been collected from the beginning of the study to the end of the study with data reduction techniques, data presentation, and conclusions. The results of this study indicate that the principal as a school leader seeks to optimally carry out his leadership duties following the concept of characteristics of school-based management objectives. This is evidenced by his role in planning, organizing, supervising, and evaluating the implementation of teaching and learning activities and administrative services running effectively and efficiently. This study concludes that school-based management in Senior High School of State I Ratahan Timur is seen as a very good government policy so that schools can be given the authority to determine the direction of school policies independently.